Research on the semantic web representation for building operation with Variable Refrigerant Flow systems. (15th September 2022) - Li, Jingming; Li, Nianping; Yue, Bao; Yan, Rui; Farruh, Kushnazarov; Li, Anbang; Li, Kehua
Abstract: Building metadata is regarded as the signpost in organizing massive building data. The application of building metadata simplifies the creation of digital representations and provides portable data analytics. Typical metadata standards such as Brick and Haystack are used to describe the data of the building system. However, neither Haystack nor Brick has provided definitions of the Variable Refrigerant Flow system so far. With the growing market for the Variable Refrigerant Flow, it is needed to have semantic descriptions of Variable Refrigerant Flow systems in metadata standards for data analysis and management. Addressing this challenge, this paper developed and verified the semantic descriptions of the Variable Refrigerant Flow system in Brick Schema. With the semantic representation, a building data management framework including a backend and a frontend has also been developed. Then, the model and the service framework are tested in an office building. Results indicated using the semantic model and the service framework reduces manpower and data analysis time. This paper provides a possible solution for the expression of the Variable Refrigerant Flow systems in the building semantic web. The works in this paper will support the semantic web in automation strategies for building management and scalable building operation. Highlights: This study used the semantic web for building energy analysis. An extended Brick module for the Variable Refrigerant Flow system is presented. A building management system is developed with the extended Brick Schema. Simultaneous data analysis can be conducted with the system. This study can improve the efficiency of building data analysis.